Robotic versus open total pancreatectomy: a systematic review and meta-analysis - Chaouch, Mohamed Ali; Gouader, Amine; Mazzotta, Alessandro; Costa, Adriano Carneiro; Krimi, Bassem; Rahbari, Nuh Nabi; Mehrabi, Arianeb; Reißfelder, Christoph; Soubrane, Olivier; Oweira, Hani (Journal of robotic surgery, 2023)
Limited data are available on postoperative outcomes in patients undergoing robotic total pancreatectomy (RTP). This systematic review and meta-analysis aimed to compare the postoperative outcomes of RTP and open total pancreatectomy (OTP). We performed a systematic review with meta-analysis according to the PRISMA 2020 and AMSTAR 2 guidelines. We included studies conducted through August 10, 2022, that systematically searched electronic databases and compared RTP with OTP. We retained four controlled clinical trials in the literature search, including 156 patients: 65 in the RTP group and 91 in the OTP group. There was no difference between the RTP group and OTP group in terms of mortality, severe complications, morbidity, bleeding, biliary leak, delayed gastric emptying, reoperation, operative time, length of stay, harvested lymph nodes, and positive resection margin. The RTP reduces the delay of the first liquid diet, first oral diet, and out of bed. RTP is feasible and safe in selected patients. Robotic surgery allows for a quicker recovery. In cases of major vessel invasion, conversion to laparotomy should be preoperatively considered.
Online veröffentlicht: 15. März 2023
Gesehen am 28.03.2024